Upaya Meningkatkan Hasil Belajar PKn Materi Negaraku Indonesia melalui Model Problem Based Instruction Berbantuan Audio Visual Siswa Kelas IV Sekolah Dasar Negeri 108239 Tanjung Mulia - Mastari Ramadhani; Nizmi Putri; Suryaningsih Suryaningsih (Medan Resource Center, 2026)
This study investigates the effectiveness of the Problem Based Instruction model in improving learning outcomes in Citizenship Education, particularly on the topic My Country Indonesia, among fourth-grade students at State Elementary School 108239 Tanjung Mulia. The research was motivated by the need to enhance students’ academic achievement and engagement in Citizenship Education learning. Employing a Classroom Action Research design based on the model developed by Suhardjono and Suharsimi Arikunto, the study involved 26 fourth-grade students, comprising 14 male and 12 female learners. The research was conducted through two action cycles, each consisting of planning, implementation, observation, and reflection stages. Data were collected using observation sheets and achievement tests. Findings from the first cycle revealed that only 73% of students achieved scores above the Minimum Mastery Criterion, indicating that the predetermined success criteria had not been attained. Following improvements in the implementation of the Problem Based Instruction model during the second cycle, the percentage of students achieving scores above the criterion increased substantially to 89.76%. These findings demonstrate that the Problem Based Instruction model effectively enhances students’ learning outcomes in Citizenship Education and contributes to a more active and meaningful learning process.